ANALISIS EFISIENSI PEMASARAN GABAH DAN NILAI TAMBAH BERAS DI KABUPATEN PESAWARAN - Eva Mulia Sari; Ali Ibrahim Hasyim; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to analyze the efficiency of paddy marketing system and value added of rice in Pesawaran District.  This research was conducted by survey method.  The research location is chosen purposively i Kota Jawa Village and Gunung Sari Village, Way Khilau Subdistrict Pesawaran District with consideration that the location is one of the central of paddy production.  The samples of this research were 51 paddy farmers who were selected by simple random sampling. The research data was collected in June–July 2017 and analyzed by descriptive and quantitative analysis.  The method used in this research is the analysis of the model of S-C-P (structure, conduct, and performance) and used Hayami method to determine the value- added of the rice.  The S-C-P model was used to analysis marketing system efficiency.  The results showed that paddy marketing system in Pesawaran District was efficient, it could be seen from the producer’s share who greater than 50%.  There were three rice milling unit (RMU) in research location and all of that rice miling unit gave a positive value-added to owner. Key words : efficiency, rice, S-C-P models, value-added